URGENSI KOMUNIKASI INTERPERONAL KBIHU KEPADA CALON JEMAAH HAJI BOGOR (Studi pada Kuliah Kerja Lapang) - Kusumadinata, Ali; Nafisha, Alma Fardatun; Wahyuni Sumah, Astrid Sri; Ernawati, Erna; Nirwana, Testa Pradia; Hasbiyah, Desi (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2024)
Hajj and Umrah are a series of Islamic pillars carried out by Muslims. Hajj and Umrah are carried out in congregation because they are carried out in other countries and have special procedures. And a companion is needed in the implementation. This study aims to describe the activities of a series on the importance of interpersonal communication in mentoring pilgrims. This research method is to carry out field lectures from the students concerned and write down a series of agendas carried out in the implementation of the mentoring. This method is known as the method of preparation. The results of this study show that the interpersonal communication approach is good and is very effective in reinforcing pilgrims. Greeting each other, knowing each other, and providing mutual support in the field provide convenience for administrative management for departure to implementation in the holy land of Makah.